2008
DOI: 10.1080/22201009.2008.10872177
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of action of oral antidiabetic drugs: A review of recent literature

Abstract: Type 2 diabetes mellitus (DM) is a disorder that is placing an increasing burden on health service delivery worldwide. Consequently, it has become increasingly important that physicians who treat such patients have a good knowledge of antidiabetic drugs that are currently available or will come onto the market. This article presents an overview of all the major drug classes as well as some information on pharmacokinetics, pharmacodynamics, side-effect profiles and indications for use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 53 publications
0
67
0
1
Order By: Relevance
“…3 As a single therapy, acarbose is less effective because it is only 2% absorbed. 4 Chronic hyperglycemia can cause many complications such as damage, dysfunction and failure of various organs, especially the eyes, kidneys, nerves, heart, and blood vessels. 1 Hyperglycemia has an important contribution in causing complications because of the trigger in free radicals reaction.…”
Section: Introductionmentioning
confidence: 99%
“…3 As a single therapy, acarbose is less effective because it is only 2% absorbed. 4 Chronic hyperglycemia can cause many complications such as damage, dysfunction and failure of various organs, especially the eyes, kidneys, nerves, heart, and blood vessels. 1 Hyperglycemia has an important contribution in causing complications because of the trigger in free radicals reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these active biological principles especially alakaloids , flavonoids and terpenoids in high concentration in the Anthocleista vogelli stem bark extracts might be responsible for the oral hypoglycaemic effects recorded in the present study. Previous studies have shown that the presence of flavonoids in plants helps in the reduction of fasting blood glucose concentration since flavonoids have been found to stimulate the secretion of insulin [14].The possible mechanism of action might be via the following mechanisms; stimulation of the pancreatic beta cells to secrete insulin, improvement of insulin sensitivity [16], slowing down absorption of carbohydrate and hence slows down glucose production [17]. Hence the higher percentage reduction by the 400 mg/kg of ME can be attributed to its high alkaloid and flavonoid contents compared to the n-hexane extract.…”
Section: Discussionmentioning
confidence: 99%
“…Availability of such fixed dose combination formulation in the market is likely to lead to the continued usage of sulfonylurea and suboptimal dosage of metformin even right from the time of diabetes diagnosis with all its effects in the patients. Difficult and likely to cause hypoglycemia if the optimal dose of metformin is targeted or maintained *Apart from the risk of effect of severe hypoglycemia on heart, it is also advised that use of the sulfonylurea types (glibenclamide, glipizide, glimepiride and others) that bind the sulfonylurea receptor-2 A and B should be avoided in high-risk patients suspected of having significant coronary artery disease [51]. † Sulfonylureas are often advised to be taken at least 15-20 minutes before a meal [51].…”
Section: Long-term Safety Profilementioning
confidence: 99%